A Comparative Analysis of Source and Target Cultures in Indonesian 10th Grade English Textbooks - Anggraini, Dilla; Rohmah, Zuliati (Universitas Jambi, Magister Program of English Education Department, 2024)
This study examines cultural representation in two Indonesian grade 10 English textbooks, Bahasa Inggris